2013
DOI: 10.1590/s0034-8910.2013047004997
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de nascimentos pré-termo por peso ao nascer: revisão sistemática

Abstract: OBJECTIVE:To estimate the prevalence of preterm birth by categories of birth weight, and to obtain an equation to correct the estimates. METHODS:Systematic review of the Brazilian literature published from 1990 to 2012, to identify studies with primary collection of data on birth weight and gestational age. Twelve studies were selected and contributed for tabulations of preterm prevalence according to 100 g birth weight categories. These results were combined using sex-specific fractional polynomial equations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 23 publications
1
11
0
7
Order By: Relevance
“…17 However, it was in the preterm strata before the physiological weight gain acceleration expected in the last 4 gestational weeks that the macrosomia frequency became more noticeable, comparing 2012-2014 to 2001-2010 in the present study. In the 2001-2010 period, the estimates were within the limits of prevalence of preterm newborns weighing between 4,000 g and 5,000 g obtained with a correctional equation provided by Silveira et al 14 For the 2012-2014 period, the estimates were higher than those found in the first period, and this probably reflects the improvement in the quality of the data from SINASC.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…17 However, it was in the preterm strata before the physiological weight gain acceleration expected in the last 4 gestational weeks that the macrosomia frequency became more noticeable, comparing 2012-2014 to 2001-2010 in the present study. In the 2001-2010 period, the estimates were within the limits of prevalence of preterm newborns weighing between 4,000 g and 5,000 g obtained with a correctional equation provided by Silveira et al 14 For the 2012-2014 period, the estimates were higher than those found in the first period, and this probably reflects the improvement in the quality of the data from SINASC.…”
Section: Discussionsupporting
confidence: 58%
“…As differences between the SINASC data and the primary data studied by Silveira et al 14 were more marked involving newborns weighing up to 3,000 g, with lower or no significant difference above this weight group, no factor was used to correct the birth weight ! 4,000 g in relation to gestational age.…”
Section: Palavras-chavementioning
confidence: 99%
“…16 It is the moment to identify diseases which can affect both baby and mother during the gestation and lead to prematurity.…”
Section: Gestational Factors N %mentioning
confidence: 99%
“…High prevalence of prematurity brings important social and economic expenses, such as growing demand for neonatal intensive care units and costs of attention at short term, and in long term, caring for individuals suffering from permanent physical and mental damages caused by prematurity (Silveira et al, 2013). In developing countries, such as Brazil, the establishing of adequate caring parameters to newborns is one of the challenges to reduce infant mortality, as 70% of infant deaths are caused by neonatal complications.…”
Section: Introductionmentioning
confidence: 99%